3D printed electronics with nanomaterials. Issue 12 (7th March 2023) - Słoma, Marcin
Abstract : This review focuses on the recent advances in the application of nanomaterials for 3D printed electronics, demonstrating conductive paths, electronic and photonic components, energy devices or sensors with perspectives for future developments. Abstract : A large variety of printing, deposition and writing techniques have been incorporated to fabricate electronic devices in the last decades. This approach, printed electronics, has gained great interest in research and practical applications and is successfully fuelling the growth in materials science and technology. On the other hand, a new player is emerging, additive manufacturing, called 3D printing, introducing a new capability to create geometrically complex constructs with low cost and minimal material waste. Having such tremendous technology in our hands, it was just a matter of time to combine advances of printed electronics technology for the fabrication of unique 3D structural electronics. Nanomaterial patterning with additive manufacturing techniques can enable harnessing their nanoscale properties and the fabrication of active structures with unique electrical, mechanical, optical, thermal, magnetic and biological properties. In this paper, we will briefly review the properties of selected nanomaterials suitable for electronic applications and look closer at the current achievements in the synergistic integration of nanomaterials with additive manufacturing technologies to fabricate 3D printed structural electronics. The focus is fixed strictly on techniques allowing as much as possible fabrication of spatial 3D objects, or at least conformal ones on 3D printed substrates, while only selected techniques are adaptable for 3D printing of electronics. Advances in the fabrication of conductive paths and circuits, passive components, antennas, active and photonic components, energy devices, microelectromechanical systems and sensors are presented. Finally, perspectives for development with new nanomaterials, multimaterial and hybrid techniques, bioelectronics, integration with discrete components and 4D-printing are briefly discussed.